Developmental and Activity Dependent Regulation of Ionotropic Glutamate Receptors at Synapses - Elek Molnar; John T.R. Isaac (The Scientific World Journal)
Glutamate receptors mediate the majority of excitatory responses in the central nervous system. The establishment and refinement of glutamatergic synaptic connections depend on the concerted actions of a-amino-3-hydroxy-5-methyl-isoxazole-4-propionate (AMPA), N-methyl-D-aspartate (NMDA), and kainate (KA) type ionotropic glutamate receptors (iGluRs) and G-protein coupled metabotropic receptors. While a lot remains to be clarified, the most is known about the mechanisms by which the iGluR subtypes are targeted and how this is influenced by synaptic activity on both short and long time scales. Changes in their subunit compositions are also input specific and developmentally regulated. The identification of key molecular components of the postsynaptic density (PSD) and novel proteins that influence receptor targeting and clustering have started to reveal the underlying molecular mechanisms of the trafficking and targeting of iGluRs. Here we discuss the evidence that these basic mechanisms are used during developmental synaptic plasticity.